2020
DOI: 10.1186/s13293-020-0284-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exercise results in morphological and biomechanical changes in coronary resistance arterioles in male and female rats

Abstract: Background: Biomechanical remodeling of coronary resistance arteries in physiological left ventricular hypertrophy has not yet been analyzed, and the possible sex differences are unknown. Methods: Wistar rats were divided into four groups: male and female sedentary controls (MSe and FSe) and male and female animals undergoing a 12-week intensive swim training program (MEx and FEx). On the last day, the in vitro contractility, endothelium-dependent dilatation, and biomechanical properties of the intramural coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
2
5
0
1
Order By: Relevance
“…4 a demonstrates that as an effect of training, wall thickness significantly increased in the 200- to 500-μm outer diameter range in males. We think that increased muscularity ensured increased range of vasomotion (between fully contracted and fully relaxed states), as has been observed in an earlier publication from our laboratory [ 25 ] with pressure arteriography for rat coronary arteriole segments in the 200-μm range. There was some sex significance in this respect: training-induced wall thickening was moderate in female (300–350 μm) vessels, and there was a characteristic thinning of the wall at the largest branches in this sex (Fig.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…4 a demonstrates that as an effect of training, wall thickness significantly increased in the 200- to 500-μm outer diameter range in males. We think that increased muscularity ensured increased range of vasomotion (between fully contracted and fully relaxed states), as has been observed in an earlier publication from our laboratory [ 25 ] with pressure arteriography for rat coronary arteriole segments in the 200-μm range. There was some sex significance in this respect: training-induced wall thickening was moderate in female (300–350 μm) vessels, and there was a characteristic thinning of the wall at the largest branches in this sex (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Substantial sex differences in endothelial relaxation have also been demonstrated with training in other vessels: the flow-mediated dilatation of the brachial artery increases in men but not in women after acute exercise [ 22 24 ]. Furthermore, the myogenic tone and the agonist-induced contraction (thromboxane agonist) of coronary arteries are greater only in female rats after strenuous physical exercise [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Echocardiographic examinations were performed to test the training status of the animals. In accordance with our previous results and published data in the literature, 12 weeks of the swim training leads to substantial myocardial hypertrophy in both males and females (Olah et al, 2019;Török et al, 2020b).…”
Section: Effect Of Strenuous Training On the Heart And Morphology And Biomechanics Of Gracilis Arteriolessupporting
confidence: 93%
“…In earlier studies, we investigated the morphological, biomechanical, and functional sex differences of coronary resistance vessels in a healthy state on the effects of hypertension and sports activities ( Matrai et al, 2007 ; Mátrai et al, 2012 ; Török et al, 2020b ). By studying coronary vessels, using an in vitro pressure myograph, we found that physical training in females led to an increase in contractility, while, in males, endothelium-related dilatation capacity was increased ( Török et al, 2020b ). This alteration observed in the male group, following long-term physical exercise, was not detected in postmenopausal women ( Pierce et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in vasoconstriction and vasodilation responses of coronary arteries in this study may be also explained by the observation that both smooth muscle elements and elastic fibers are altered by gender and vitamin D deficiency. The amount of elastic fibers of resistance coronary arteries is significantly lower in male rats than in females [ 40 ]. Previous studies examining the effect of vitamin D deficiency on elastic elements showed that abdominal aortic aneurysms have significantly lower levels of elastin in the intima-media composites of male aneurysm walls than of females [ 41 ].…”
Section: Discussionmentioning
confidence: 99%